2007
DOI: 10.1007/bf02698043
|View full text |Cite
|
Sign up to set email alerts
|

CEA levels in serum and BAL in patients suffering from lung cancer

Abstract: CEA levels in BAL of normal individuals may be influenced by smoking and other factors that affect lung epithelial cell function. Thus, CEA measurement in BAL alone has little value in the diagnosis of malignancy. BAL CEA levels in smokers of G2 are found significantly higher compared with nonsmokers of the same group and healthy individuals. Smokers of G2 have to be followed up carefully for the possibility of lung cancer growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…[15] Unlike CEA, DR-70 floats freely in blood and abundant in serum acts as a “barometer for cancer” by simultaneously measuring the multiple FDP species that may be underestimated by other tests. [161718] DR-70 detects all of the breakdown products of Fibrin and Fibrinogen, including a unique “IPDP” cancer-related breakdown product. DR-70 is different from estimation of D-dimer as D-dimer values alone would greatly underestimate cancer and miss some altogether.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Unlike CEA, DR-70 floats freely in blood and abundant in serum acts as a “barometer for cancer” by simultaneously measuring the multiple FDP species that may be underestimated by other tests. [161718] DR-70 detects all of the breakdown products of Fibrin and Fibrinogen, including a unique “IPDP” cancer-related breakdown product. DR-70 is different from estimation of D-dimer as D-dimer values alone would greatly underestimate cancer and miss some altogether.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating specific molecular markers in airways might serve as an important adjunct to routine examination for lung cancer diagnosis. The utility of cytokines in bronchoalveolar lavage fluid (BALF) for differential diagnosis of lung cancer has been described in several studies6789101112. In our previous reports, we also observed that the levels of vascular endothelial growth factor (VEGF) and neuron-specific enolase (NSE) were significantly higher in BALF of lung cancer patients than in that of patients with benign diseases1314.…”
mentioning
confidence: 90%
“…In contrast, only a few studies have investigated CEA concentrations in BALF. Charalabopoulos et al 10 measured CEA in BALF among 50 patients with lung cancer, 20 benign lung lesions, and 20 healthy controls. In support of our findings, they demonstrated that CEA measurement in BALF alone has little value in the diagnosis of malignancy.…”
Section: Disscusionmentioning
confidence: 99%
“…Changes of cytokines in bronchoalveolar lavage fluid (BALF) reflect immunologic reactions of the lung in pulmonary malignancies4. Thus, detection of biomarkers in BALF might serve as an important adjunct to bronchoscopy for differential diagnosis of lung cancer567891011. In our previous study, we found that the level of vascular endothelial growth factor (VEGF) was significantly increased in both serum and BALF among patients with lung cancer12.…”
mentioning
confidence: 99%